Evaluation of Tensile Bond Strength between Dentin and Metallic Copings Using Different Resin Cements - Ehsan Ghasemi; Mansour Rismanchian; Navid Haghayegh (Mashhad University of Medical Sciences, 2018)
Statement of the Problem: For a successful clinical outcome, luting agents should have a high bond strength. Bond failure is still one of the main reasons of restoration failures. Purpose: The present study was designed to comparatively evaluate the retention of metallic copings using different resin luting cements. Materials and Method: In the present experimental study, 40 intact premolar teeth were included. The teeth were prepared to receive copings with a chamfer bur at high speed, cooled with an air/water spray. The occlusal surface was prepared flat, perpendicular to the long axis of the root at a standardized height of 4 mm from the gingival chamfer finish line with a 20 degree consistent taper of axial walls. The wax patterns were prepared and cast. Teeth with un-cemented casts were randomly divided into 4 groups based on the type of cement used. The tensile load required to dislodge the crowns was measured using Instron universal testing machine with a crosshead speed of 1mm/min. The data were analyzed by SPSS software and Kruskal-wallis test (a=0.05). Results: The maximum and minimum amounts of crown retention were in Panavia-F2 and Maxcem cements respectively. Despite this different retention values in cements, Kruskal-wallis disclosed no significant difference between groups in the mean amount of crown retention. (P-Value=0.068)Conclusion: Regarding the results of the study, it was concluded that there are no mentionable differences between all groups.